I got this : how I changed my ways and lost what weighed me down - Hudson, Jennifer, 1981- (New York : E.P.Dutton, 2012)
This memoir tells the story of Jennifer's rise from American Idol to Dreamgirls to her amazing weight loss on the Weight Watchers diet.
Keywords: Hudson, Jennifer, -- 1981-; Singers -- United States -- Biography; Weight loss -- United States -- Biography; Weight loss -- Popular works